Penerapan Hermeneutika Modern dalam Menafsirkan Teks - Andressa Muthi’ Latansa (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2022)
Abstract As a new perspective that brings great influence in the study of contemporary Religion, the presence of hermeneutics in turn also influences the study of Islam. The presence of hermeneutics in Islamic studies is of course originated from the character of Islamic thought, as almost all types of religious thought, which tend to be multi-interpreted. The following text is generally more likely to see the influence of hermeneutics on Islamic Studies and more specifically its influence on the interpretation of the Qur’an.